2007
DOI: 10.2140/jomms.2007.2.1309
|View full text |Cite
|
Sign up to set email alerts
|

Protection performance of double-layered metal shields against projectile impact

Abstract: This paper critically evaluates the protection performance of double-layered shields against projectile impact at the subordnance velocity using finite element methods. Four types of projectiles of different weight and nose shape are considered, representing various fragments generated from Improvised Explosive Devices (IEDs). It is found that the double-layer configuration is able to improve the ballistic resistance by 8.0%-25.0% for the flat-nose projectile, compared to the monolithic plate of the same weigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
36
1
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(42 citation statements)
references
References 24 publications
4
36
1
1
Order By: Relevance
“…However, 12 mm monolithic plate presented a slightly better performance for striking velocities above 850 m/s. A recent investigation by Teng et al [3,8] on the ballistic performance of monolithic and double-layered steel plates showed that the ballistic resistance depends on several factors, including projectile nose shape, projectile mass, impact velocity, configuration of the plates and material properties. Corran et al [9] found that the projectile nose shape and hardness are very important to consider because the failure mechanisms involved in the penetration process and consequently the ballistic performance are dependent upon these factors.…”
Section: Introductionmentioning
confidence: 99%
“…However, 12 mm monolithic plate presented a slightly better performance for striking velocities above 850 m/s. A recent investigation by Teng et al [3,8] on the ballistic performance of monolithic and double-layered steel plates showed that the ballistic resistance depends on several factors, including projectile nose shape, projectile mass, impact velocity, configuration of the plates and material properties. Corran et al [9] found that the projectile nose shape and hardness are very important to consider because the failure mechanisms involved in the penetration process and consequently the ballistic performance are dependent upon these factors.…”
Section: Introductionmentioning
confidence: 99%
“…Very generally, the performance of multi-layer armor is affected by the shape of the projectile, with blunt ogives being more easily defeated [1,43]. The impact-induced phase transition, which is a primary source of energy dissipation for the designs herein, relies on rapid compression of the polymer coating by the projectile.…”
Section: Methodsmentioning
confidence: 99%
“…The impact resistance of multiple thin metallic plates has been found to be better [1,2] or worse [3,4] than that of fewer thick plates, the relative performance depending on the materials, their arrangement, and the shape of the projectile ogive [5,6,7]. Polymers are eight times less dense than steel and thus an obvious route to lighter structures.…”
Section: Introductionmentioning
confidence: 99%
“…Teng et al, [10] evaluated the effect of projectile with different nose shape and weight shot on monolithic and double-layered plate by using the finite element method. The result of the simulation showed that the double-layered plate was more ballistic resistant 8.0%-25.0 % for the flatnose projectile, compared to the monolithic plate of the same weight.…”
Section: Introductionmentioning
confidence: 99%